Keberhasilan program dinas sosial kota malang dalam pemberdayaan tunawisma untuk mengurangi angka kemiskinan - Anggraini, Annisa Rani (Maliki Interdisciplinary Journal, 2025)
Poverty and homelessness are complex and interrelated social problems. Homeless people are often trapped in a cycle of poverty due to lack of access to education, employment, and shelter. Empowering homeless people is an important strategy in reducing poverty. One example of the implementation of homeless empowerment can be observed in the programs run by the Malang City Social Service which provides assistance and training to homeless people so that they can be economically and socially independent. The purpose of this research is to analyze and explore the success of the Malang City Social Service program in empowering homeless people in Kampung Topeng. The approach used in this research is qualitative with a case study method and data collection using observation and interview techniques. The result of this research is that the program provided by the Social Service of Malang City is still not successful in handling homeless empowerment in Kampung Topeng, this can be seen from the large number of residents who return to the streets to make a living.